In vitro Antioxidant, Anti-Inflammatory, Anti-venom and Anti-cancer Effect of Leucas aspera Plant Extract - Sumathi, Raguraman (Asian Journal of Biological and Life Sciences, 2025)
Aqueous extract of Leucas aspera was evaluated for antioxidant, anti-inflammatory, antivenom and anticancer activities using in vitro assays (DPPH, OH scavenging, COX/LOX inhibition, MTT). Results indicate significant antioxidant and selective anticancer activity against HepG2 cells along with PLA2 inhibition, supporting traditional usage.
Keywords: Leucas aspera; Antioxidant; Anti-inflammatory; Anticancer